THE TOURISTS’ SPATIAL BEHAVIOUR AND TOURIST MOVEMENT PATTERN IN MUAR JOHOR - M Noor Azman, Nor Afifin Nadia; Abd Rahman, Nur Hidayah; Md Sawari, Siti Salwa; Abas, Siti Aisah; Abdul Latif, Samshul Amry (PLANNING MALAYSIA, 2021)
Unsystematic transportation system and accessibility, fewer tourism packages supply, and disorganised digital marketing strategy in destination management are the factors of the limitation of the tourist movement in a destination. Therefore, this research aims to determine the characteristics of the tourist’s spatial behaviour and tourist movement pattern in Muar, Johor. This research implemented a qualitative method through the semi-structured interview, which involved seven respondents who visited Muar, Johor. The result shows the characteristics of tourists’ spatial behaviour and tourist’s movement pattern has a significant interaction in investigating visiting characteristics, spatial data and movement. In the context of the macro-level movement pattern, the findings indicate that Muar has the potential to be developed as a one-day trip and three days one-night trip destination. Hence, it has positively affected tourism destination management to improve the travel package for domestic and international tourists. The main contribution of this research is to apply the mutual understanding of the tourist movement concept among visitors in investigating the complex visitor movement during travel related to the physical environment factor such as attractions, route and accessibility, and mode of transportation influenced by tourists’ spatial behaviour. This study can also be a primary reference for Muar local authority and destination management to ameliorate many aspects of creating an efficient tourist movement considering sustainable development in the urban heritage area.